Optimal vaccination strategies for 2009 pandemic H1N1 and seasonal influenza vaccines in humans - Wu, J; Zhong, X; Li, C; Zhou, J; Lu, M; Huang, K; Dong, M; Liu, Y; Luo, F; Du, N; Chui, C; Liu, L; et al. (2011)
A randomized clinical trial was conducted to assess whether the immunogenicity of seasonal and pandemic (H1N1/09) influenza vaccines is affected by the order of vaccine administration. 151 healthy adult volunteers were randomized into three groups. All groups received one dose (15 μg haemagglutinin) each of a pandemic H1N1 vaccine and a seasonal trivalent vaccine. Group 1 received the pandemic H1N1 vaccine first, followed by the seasonal vaccine 21 days later. Group 2 received vaccinations in vice versa and Group 3 received both vaccines simultaneously. Post-vaccination blood samples were collected to determine the immunogenicity by hemagglutination-inhibition (HI), microneutralization (MN), and B cell ELISPOT assays. All three vaccination strategies were well-tolerated and generated specific immune responses. However, we found a significant difference in magnitude of antibody responses to pandemic H1N1 between the three groups. Pre- or co-vaccination with the seasonal flu vaccine led to a significant reduction by 50% in HI titre to pandemic H1N1 virus after pandemic vaccination. Pre- or co-vaccination of pandemic H1N1 vaccine had no effect on seasonal flu vaccination. MN and ELISPOT assays showed a similar effect. Vaccination with pandemic H1N1 vaccine first is recommended to avoid an associated inhibitory effect by the seasonal trivalent flu vaccine. Clinical_Trials identifier: NCT01008137. © 2010.